2008
DOI: 10.1124/dmd.108.023929
|View full text |Cite
|
Sign up to set email alerts
|

The Carnitine TransporterSLC22A5Is Not a General Drug Transporter, but It Efficiently Translocates Mildronate

Abstract: ABSTRACT:In addition to its function as carnitine transporter, novel organic cation transporter type 2 (OCTN2; human gene symbol SLC22A5) is widely recognized as a transporter of drugs. This notion is based on several reports of direct measurement of drug accumulation. However, a rigorous, comparative, and comprehensive analysis of transport efficiency of OCTN2 has not been available so far. In the present study, OCTN2 orthologs from human, rat, and chicken were expressed in 293 cells using an inducible expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 25 publications
2
42
1
Order By: Relevance
“…Further clinical studies are required to determine the toxicological relevance of OCTN2 to CER-induced nephrotoxicity. Grigat et al (2009) recently reported that OCTN2 does not transport CER, whereas the present findings suggest the involvement of OCTN2 in renal secretion of CER. One of the possible explanations for such discrepancy would be the species difference in the function A, oocytes injected with cRNA for mouse OCTN2 (F) or water alone (E) were incubated with 1 mM CER, and uptake for designated periods was determined.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Further clinical studies are required to determine the toxicological relevance of OCTN2 to CER-induced nephrotoxicity. Grigat et al (2009) recently reported that OCTN2 does not transport CER, whereas the present findings suggest the involvement of OCTN2 in renal secretion of CER. One of the possible explanations for such discrepancy would be the species difference in the function A, oocytes injected with cRNA for mouse OCTN2 (F) or water alone (E) were incubated with 1 mM CER, and uptake for designated periods was determined.…”
Section: Discussioncontrasting
confidence: 56%
“…Uptake of CER was then measured, and OCTN2-mediated uptake was obtained by subtracting the uptake by water-injected oocytes from that by oocytes expressing OCTN2. of OCTN2 because they examined OCTN2 ortholog from human, rat, and chicken (Grigat et al, 2009), whereas we checked mouse OCTN2 (Figs. 5 and 6).…”
Section: Discussionmentioning
confidence: 99%
“…Note that Tamai and coworkers used tritium-labeled chemicals in their study. A conceivable risk of the use of radiotracers in uptake assays is that small radiolabeled fragments generated by chemical decay of the radiotracer are scored by liquid scintillation counting like the original compound; thus, the signal in transporter-positive lysates could originate from fragments, but not from the intact radiotracer (Grigat et al, 2009). Tandem mass spectrometry (LC-MS/MS), by contrast, has the advantage of high specificity because in selected reaction monitoring mode molecules will be detected only if they pass two separate mass filters.…”
Section: Figurementioning
confidence: 99%
“…At a dose of 100 mg/kg, the mildronate concentration in rat blood plasma reached 20 μM after a single administration; however, after 3 days of repeated administration, the mildronate concentration remained at 20 μM even 24 h after the last administration (Liepinsh 2006). Mildronate is actively transported into tissues by OCTN2 (Grigat et al, 2009), and the mildronate concentration in liver and heart reaches 500-1000 μM . Thus, mildronate concentrations are able to completely inhibit L-carnitine biosynthesis and substantially decrease L-carnitine transport into tissues and reabsorption in the kidneys.…”
Section: Inhibitory Effect Of Mildronate On L-carnitine Contentmentioning
confidence: 99%